A point-like thermal light source as a probe for sensing light-matter interaction - Korn, Sascha; Popp, Matthias Albert; Weber, Heiko B. (Scientific Reports, 2022)
Historically, thermal radiation is related to 3D cavities. In practice, however, it is known that almost any hot surface radiates according to Planck’s law. This approximate universality roots in the smooth electromagnetic mode structure of free space, into which the radiation is emitted. Here, we study the effect for a strongly patterned mode structure and use quasi-transparent point-like thermal light emitters as a probe. As such, we choose current-driven graphene nanojunctions for which the emission into free space obeys Planck’s law. Placed in front of a mirror, however, this process is highly sensitive to a node/antinode pattern of light modes. By varying the distance, we can sample the latter with atomic precision, and observe a deep imprint on the observed spectrum. The experiment allows an unprecedented view on thermal radiation in a spatially/spectrally patterned electromagnetic environment.<br

Noble Gas Provides a Solution to the Synthesis‐On‐Inert‐Surfaces Challenge for Extended Covalent Nanostructures - Grossmann, Lukas; Korn, Sascha; Breuer, Rochus; Schmittel, Michael; Weber, Heiko B.; Heckl, Wolfgang M.; Lackinger, Markus (Angewandte Chemie International Edition, 2025)
A key milestone in the field of On-Surface Synthesis (OSS) is the development of generic protocols for covalent coupling on inert surfaces. Typically, metal surfaces are used in OSS, but the strong interactions distort the intrinsic properties of the synthesized nanostructures and therefore compromise their applicability. Inert surfaces, on the other hand, preserve the nanostructures’ unique properties, but present challenges during synthesis: Activation energies are generally higher than on metal surfaces, hence thermally activated coupling on inert surfaces is severely hampered by competing premature desorption of the reactants. Using the coupling of 1,3,5-tris(4-mercaptophenyl)benzene (TMB) via carbon-sulfur-carbon thioether bonds, we demonstrate that annealing in a noble gas atmosphere instead of in a vacuum kinetically inhibits desorption. This allows covalent coupling on both inert graphite and even more weakly interacting graphene surfaces. We anticipate generic potential for this approach, with future experiments exploring the expandability of ambient pressure annealing to a portfolio of other coupling protocol
CRIS-Team Scopus Importer:2025-02-28
Keywords: graphene; graphite; inert surfaces; on-surface synthesis; Sierpinski triangle

The Squeezable Nanojunction as a tuneable light-matter interface for studying photoluminescence of 2D materials - Popp, Matthias Albert; Kohring, Malte; Fuchs, Alexander; Korn, Sascha; Moses Badlyan, Narine; Maultzsch, Janina; Weber, Heiko B. (2D Materials, 2021)